2014
DOI: 10.1259/dmfr.20130392
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compression force on elasticity index and elasticity ratio in ultrasound elastography

Abstract: Objectives: The purpose of this study was to investigate the relationship between compression force and hardness values in ultrasound elastography. Methods: Ultrasound elastography was performed using an elastography phantom, comprising inclusions with different elasticities and echogenicities. The compression force was set to approximately 100 gw (light force) and approximately 500 gw (heavy force). The elasticity index (EI) of the inclusion was measured. The EI was a relative hardness value of a structure wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
2
6
0
Order By: Relevance
“…Acute clots underwent less strain (deformation) and showed a higher EI than chronic clots. In agreement with previously described investigations , we also demonstrated that simply the assessment of a single and basic UE parameter such as the EI could almost perfectly discriminate an acute DVT from a chronic DVT. The diagnostic accuracy of this value was nearly comparable to the accuracy of the D‐dimer assay tested in this population.…”
Section: Discussionsupporting
confidence: 92%
“…Acute clots underwent less strain (deformation) and showed a higher EI than chronic clots. In agreement with previously described investigations , we also demonstrated that simply the assessment of a single and basic UE parameter such as the EI could almost perfectly discriminate an acute DVT from a chronic DVT. The diagnostic accuracy of this value was nearly comparable to the accuracy of the D‐dimer assay tested in this population.…”
Section: Discussionsupporting
confidence: 92%
“…18 Another study comparing the EI with the elasticity ratio (ER), latter obtained as the ratio of EI of the lesion and EI of the reference, suggested that EI may solely be used for evaluation of soft tissues. 19 We also found ECI (same as EI) to have a high diagnostic accuracy, to be easily reproducible and more objective. We suggest that ECI, a quantitative elastography parameter, must be utilized for further characterization of the lesion in addition to conventional sonography, whenever available in the ultrasonography unit.…”
Section: Discussionmentioning
confidence: 58%
“…An experimental study clarified that the location of the reference areas did not affect the strain ratio, which corresponded to the EI ratio in the present study when the objective area was surrounded by a homogeneous structure in which the reference ROIs were set. 13 This condition, however, is rarely found, especially in in vivo examinations of skeletal muscles. Although subcutaneous fat with enough thickness might be a suitable reference when the strain values (the EIs) can be measured and can be used for comparison of values of an individual, it is not adequate for comparing such values between individuals.…”
Section: Discussionmentioning
confidence: 99%